The Effect of Cyberloafing and Psychological Improvement on Engagement Mediated by Job Satisfaction - Geubirina, Thera Najwa Ajeng Java; Ambarwati, Diana; Akbar, Taufik (Jurnal Manajemen (Edisi Elektronik), 2025)
This research aims to examine how the level of work empowerment among employees at PT Citra Warna Abadi influences their innovative work behavior. The study involved 79 respondents, consisting of both current and former employees of PT Citra Warna Abadi, selected through a non-probability sampling method with a purposive component. Data was collected using a questionnaire in this quantitative research study. Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method was used to analyze the data, utilizing the SmartPLS version 4.0 application.The results reveal a positive and statistically significant relationship between job engagement and creative actions at work. Additionally, work empowerment is positively and significantly influenced by employee engagement. When employees feel empowered in their roles, they are more likely to act creatively and independently. Job engagement also impacts innovative work behavior indirectly through work empowerment. This study suggests that PT Citra Warna Abadi can enhance its employees' creative output by improving their job engagement. Therefore, factors like employee engagement, which significantly influence innovative work behavior, should receive greater attention from the company. The findings highlight the importance of work empowerment in fostering a workplace environment conducive to creativity and innovation. Future research could explore the role of other organizational factors, such as workplace culture and leadership, in driving employees’ innovative work behavior.